(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Taking into account of Chitosan and its potential for commercialization as well as their effects on the environment and their ranges of possible uses are explored in this review. A survey of the literature was used to conduct this investigation. Many types of aquatic crustaceans like crabs and shrimp, as well as numerous insects, as well as fungus, include chitin. One of the industries in the world that is growing the fastest is the shrimp industry. But the hard exoskeleton of shrimp, including the parts of the shrimp skin and head, is thrown away as bio-waste during the processing of shrimp. Chitin is present in significant amounts in the shrimp exoskeleton. The deacetylation process turns chitin into the bioproduct chitosan. The deacetylation process can be carried out by chemical or biological methods. A significant amount of bio-waste treated with chitin can be converted into chitosan.